Checklist of sponges (Porifera) at the shelf-break front of Argentina, SW Atlantic Ocean, with data on their settlement substrata - Schejter, Laura (2025)
A checklist of the sponges recorded in Argentina’s shelf-break front between 37° and 45°S as well as the settlement substratesthey used is provided here. A total of 45 sponge species were reported in the study area from samples obtained during stockassessment cruises of the Patagonian scallop Zygochlamys patagonica (P.P. King, 1832), with an addition of 10 species frombibliographic sources, totalling 55 Demosponge species. Considering that the region is characterized mainly by the presence ofsoft sandy bottoms, living molluscs or their empty shells were found to be the main substrate for the majority of the recordedspecies (in particular, on Fusitriton magellanicus (Röding, 1798) and Z. patagonica). Polychaete tubes represented the second mostimportant biogenic settlement substrate for sponges in the study area. Epibiotic sponges also increase the structural complexity ofthe ecosystem by forming microhabitats that can be exploited as refuges for other small species, thus enhancing local biodiversity.